A Sociological Study on University Students' Problems and Their Family Context: With Special Reference to the University of Sri Jayewarcienepura - Perera, M.A.N.R.M. (University of Sri Jayewardenepura, Nugegoda, 2010)
Education is one of basic needs and in turns a right of all human beings. Even though, universities are considered as excellent centres for education, some students cannot gain its' full benefits due to the various reasons including students' problems. Student problems affect severely on their learning. Most of problems are multifaceted and arisen due to multiple reasons. A purposeful and conscious attempt by each stakeholder is needed to establish a proper learning atmosphere in universities. This means that for a proper learning environment, responsibility of university as well as families of students are equally important. Even though the university authority has already taken several steps in reforming university system, without having proper knowledge of students' problems it would not be easy to analyse such problems. Wrong or inadequate analysis of these problems is another problem in planning, implementing of solutions, and in turns gaining expected results successfully. This study identified a triangular relationship regarding the university students' problems as problems arisen due to students' personal qualities, their family backgrounds and education institution. The main objective of this study is to investigate the students' problems and relationship with their family backgrounds. This objective was achieved through examining students' personal background related problems, examining students' family background related problems, identifying problems related to the university environment, and to disseminating the findings of the research in order to educate stakeholders of the university education for the policy decisions. University of Sri Jayewardenepura was selected as the field of study. It was selected a sample of students including 1000 students as 400 from Faculty of Management Studies and Commerce, 300 from Faculty of Arts, 150 from Faculty of Science and 150 from Faculty of Medicine. Data collection was made by means of Questionnaire Survey, Group Discussions, In-depth Interviews, and Contacting Experts. Collected data were tabulated into tables and charts according to the necessity to trace distinguished set objectives using SPSS software. Secondly, by synthesizing and analyzing gathered data and theory, critical discussions were made to reach the objectives of the study. For this purpose, statistics such as Mode, Mean, Medium, Percentage etc were applied. Descriptive analysis technique was mainly adopted. This study clearly found that there is a closer relationship between students' problems and socio-economic backgrounds of their families. Except some specific problems that are directly related with the education institution such as examination problems, inadequate resources, workload etc, almost all other problems are directly or indirectly related with students' family backgrounds. At the same time, students in the Arts faculty have more problems than the other students. Finally, it is proposed some new researchable problems such as "The effectiveness of institutional efforts in analysing students' problems", "The effectiveness of mechanisms that students take to solve their problems", and "How do parents keep eye on their students' education at the university?" In fact, these are possible new research on the same issue in three different angles.